2008
DOI: 10.4012/dmj.27.7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermal Cycling Effects on the Flexural Strength of Glass Ceramics Fused to Titanium

Abstract: This study evaluated the effects of mechanical and thermal cycling on the flexural strength (ISO 9693) of three brands of ceramics fused to commercially pure titanium (cpTi). Metallic frameworks of 25×3×0.5 mm dimensions (N=84) were cast in cpTi, followed by 150-μm aluminum oxide airborne particle abrasion at a designated area of the frameworks (8×3 mm). Bonder and opaque ceramic were applied on the frameworks, and then the corresponding ceramic (Triceram, Super Porcelain Ti-22, Vita Titankeramik) was fired on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
42
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 34 publications
8
42
0
1
Order By: Relevance
“…Besides, the difference in the thermal expansion coefficients of both materials may cause adhesive loss from temperature variations (7). In orthodontics, the number of thermal cycles varies from 500 to 6,000 (5,8,10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the difference in the thermal expansion coefficients of both materials may cause adhesive loss from temperature variations (7). In orthodontics, the number of thermal cycles varies from 500 to 6,000 (5,8,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…It is most recommended because it reproduces the stresses caused at the bonding resin/enamel and bonding resin/bracket interfaces during alignment, leveling and sliding movements in the orthodontic treatment. The durability may be influenced due to heavy forces produced by archwire (2), the action of water-saliva storage (6), thermal and mechanical cycling test to simulate the oral conditions prior to mechanical tests (5,7).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, temperature changes in the mouth have a negative effect on promoting crack growth over a prolonged period. By the same token, reports have emerged on the effects of thermal cycling on the flexural strength of metal-ceramic complexes 5,6) , marginal adaptation of metal-ceramic restorations 7) , and fracture strength of resin-bonded, all-ceramic fixed partial dentures 8) . However, information is scarce on the effects of thermal cycling on dental porcelain.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal cycling test has been recommended and used to verify if temperature changes may influence the reduction of bond strength values between the ceramic surface, bonding materials and brackets 2 . Previous studies showed that the reduction of the bond strength could be due to continuous action of the water on the ceramic-bonding materials-brackets interface with hydrolytic degradation of the components 24 . In addition, different thermal expansion coefficients and abrupt temperature changes of bonding materials can produce thermal stresses at the interface and decrease the bond strength 24 .…”
mentioning
confidence: 99%
“…Previous studies showed that the reduction of the bond strength could be due to continuous action of the water on the ceramic-bonding materials-brackets interface with hydrolytic degradation of the components 24 . In addition, different thermal expansion coefficients and abrupt temperature changes of bonding materials can produce thermal stresses at the interface and decrease the bond strength 24 .…”
mentioning
confidence: 99%